The Relationship between Understanding Moral Norms and Social Attitudes of Students at State Junior High School 139 Jakarta (Universitas Negeri Semarang, 2021)
This study aims to obtain empirical data about whether or not there is a relationship between understanding of moral norms and social attitudes of students at SMP Negeri 139 Jakarta. The method used in this study uses a quantitative approach with a correlational method. The sampling technique used is simple random sampling, with a total sample of 72 seventh grade students at SMP Negeri 139 Jakarta. Judging from the calculation of the Hypothesis Test with the Product Moment Correlation technique, it was found that the Relationship between Understanding Moral Norms and Social Attitudes was moderate. The understanding of the material on moral norms contributes to social attitudes with the interpretation of the coefficient of determination, which is quite significant.